Dietary Habits of Students Enrolled in Faculties of Health Sciences: A Cross-sectional Study - Aljohani, Sarah (2019)
Introduction It is often presumed that students of health sciences are more vigilant about their diet. This study assessed the prevalence of unhealthy dietary habits and identified its associated factors among students enrolled at a large university for health sciences in the Middle East. Methods A cross-sectional study, using a set of pre-validated and anonymous dietary tools, was conducted in 2018. The self-reported students’ characteristics and prevalence of 10 unhealthy dietary habits were collected. Results Males were significantly more likely have irregular meal times (β = 0.425, adjusted [adj.] odds ratio [OR] = 1.5) and insufficient seafood consumption (β = 0.55, adj. OR = 1.7) compared to females, adj. P = 0.046 and adj. P = 0.012, respectively. Students in their third year and above (β = 0.857, adj. OR = 2.2) reported more insufficient water intake compared to students in the first and second years, adjusted P = 0.003. Obesity in students was a significant associated factor with fast food consumption (β = 0.48, adj. OR = 1.8), night-eating habits (β = 0.27, adj. OR = 1.3) and skipping meals (β = 0.41, adj. OR = 1.5) compared to normal weight students, adjusted P = 0.002, adj. P = 0.004, and adj. P = 0.003, respectively. Conclusions Compliance with healthy dietary habits among students was less than optimal. Special consideration should be paid to gender and obesity that have been associated with insufficient water intake, irregular meal times, skipping meals, night-eating habits, and fast food consumption.